You can help in this new outreach in Irian Jaya at Soba and Holuwon - Regions Beyond Missionary Union; University of Edinburgh; Adam Matthew Digital (Adam Matthew Digital, 1972)
RBMU pamphlet describing its work in Kalimantan and Irian Jaya and requesting volunteers and donations